5. Penerapan Metode Role Playing Melalui Media Audiovisual Dalam Meningkatkan Aktivitas Dan Prestasi Belajar Bahasa Indonesia Siswa Kelas V Di Madrasah Ibtidaiyah Hidayatul Mubtadi’in Dukun Gresik Tahun Pelajaran 2015-2016 - ., Kurniasari; Syadiyah, Halimatus (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
Based on observations and interviews in class V MI Hidayatul Mubtadi'in Shaman Gresik, found problems in learning Indonesian. This is due to lack of optimization of the use of methods and media for effective learning by teachers. Based on the value of learning outcomes successive grade repetition 2014/2015 school year, only 10 of the 22 students (45.45%) that reached KKM is 70. Hence the need for an improved method of learning is through the application of role playing through audiovisual media. The research problems are (1) Does the application of methods Role Playing using audiovisual media can enhance learning activities in Indonesian subjects in class V MI Hidayatul Mubtadi'in Shaman Gresik in academic year 2015-2016? (2) Does the application of methods Role Playing using audiovisual media can improve student learning outcomes in Indonesian subjects in class V MI Hidayatul Mubtadi'in Shaman Gresik in the academic year 2015-2016.               This study aims to (1) increase the activity of learning through the application of methods Role Playing use Audiovisual media on the subjects of Indonesian students in class V MI Hidayatul Mubtadi'in Shaman Gresik, (2) improve learning outcomes through the application of methods Role Playing using audiovisual media on learning Indonesian students in class V MI Hidayatul Mubtadi'in Shaman Gresik. This classroom action research consists of four stages: planning, implementation, observation, and reflection carried out with two cycles, each cycle consisting of two meetings. Subjects were teachers and 22 students of class V MI Hidayatul Mubtadi'in Shaman Gresik.               Data collection techniques using tests and observation techniques, data analysis technique consists of quantitative and qualitative techniques. The results of the research activities of teachers in the first cycle obtained a score of 22 in both categories, on the second cycle to 28 with very good category. Activities of students in the first cycle obtained mean score of 19.09 with both categories, on the second cycle into 21.77 with very good category. While the classical completeness of learning outcomes in the form of quantitative data of student achievement, the first cycle of students learning completeness percentage reached 50.00% and the second cycle be 86.36%.               Based on the results of the study concluded that 1) Application of Role Playing using audiovisual media can enhance learning activities in Indonesian subjects in class V MI Hidayatul Mubtadi'in Shaman Gresik in the academic year 2015-2016. 2) Application of Role Playing using audiovisual media can improve student learning outcomes in Indonesian subjects in class V MI Hidayatul Mubtadi'in Shaman Gresik in the academic year 2015-2016. Suggestions for teachers should use the method of role playing through audiovisual media as one of the solutions to improve the activity and student achievement.